Termite Resistance of Pinus radiata D. Don Wood after Unified Thermal and Neem Seed Oil Treatment - Bhoru, Yasir Ullah; Tripathi, Sadhna (Indian Forester, 2016)
The present study was conducted to investigate the influence of unified thermal and neem seed oil treatment on the termite resistance of Pinus radiataÂ D. Don wood. For this purpose, wood was heated at different temperatures i.e. 180, 200 and 220?C for periods of 30, 60 and 90 min in an inert atmosphere and then submerged in neem seed oil (diluted to 25% with linseed oil) for 24 h. Thermal treatment at similar temperatures and time durations, Dip treatment in 25% neem seed oil and 100% linseed oil were also performed on wood to find out the role played by each component. Results revealed that untreated Pinus radiata wood is susceptible to termite and very heavy attack in ground contact was observed. Thermal treatment alone had not efficiently protected wood against termite. Neem seed oil increased resistance of wood against termite attack and only slight to moderate attack of termite was recorded in treated wood. Unified thermal and neem seed oil treatment was found effective in controlling termite attack. It was further observed linseed oil was not efficacious of reducing termite attack on wood.